Production of sustainable pavement with oil sludge - Al-Tamimi, Adil (2014)
Oil sludge (OS) has been used as partial replacement of asphalt binder for road asphalt production. The properties of OS were studied and the results showed that it has high content of heavy oil. The oil removal from OS using the solvent extraction process showed the limitation of removing heavy oil content. The maximum removal of oil content was equal to 47%. This means that the remaining residue cannot be landfilled or disposed because of the high amount of heavy oil which contains heavy metals. OS was added to asphalt binder in specific amounts just to keep the properties of the final asphalt material within standard specification limits. Three percentages of OS to asphalt binder material were studied. Many tests were performed such as Marshall design experiment, penetration, flash point, softening point, stability and flow and loss of stability. The resultant tests of softening point, penetration point, stability, loss of stability, stiffness and flow showed the possibility of using 4% of this material as one of the materials of asphalt binder.